Soil Salinity Research in 21st Century in Pakistan: Its Impact on Availability of Plant Nutrients, Growth and Yield of Crops. Issue 3 (4th February 2021) - Syed, Aaima; Sarwar, Ghulam; Shah, Sabir Hussain; Muhammad, Sher
ABSTRACT: Salinity is affecting a large area of Pakistan. The country is situated in a semiarid and arid region where the climate is subtropical continental and the process of salinization and sodification is in progress. Excessive salt rates are adversely influencing the biological, chemical, and physical properties of soils. These physical and chemical changes influence the activity of soil microbes and plant roots, and eventually affect the crop growth and yield. Therefore, it is essential from the food security viewpoint to bring these salt-affected lands into agriculture production for the promptly growing population. The paper provides a brief overview of the different aspects of salt-affected soils regarding their extent, origin, existence, nature, types, causes, characteristics, visual diagnosis, effects on soils and plants, salttolerant plant species, management, strategies adopted in Pakistan to overcome salinity, saline, and bio-saline agriculture. Different issues of salinity can be managed by adopting strategies that are helpful in reclamation of such soils. The overview focuses on chemical and biological amendments as they are the most effective implements in improving various soil properties (soil permeability and structural stability) of saline/sodic soils for sustainable food production, thus, authenticating the potential of inorganic and organic amendments to reinstate soil quality. Salinity effects can be reduced to a higher level by the addition of fertilizers and these amendments may also improve nutrient use efficiency. Other sustainable agronomic practices (crop diversifications, leaching by irrigation water, scraping, etc are also pointed out that may inhibit and, in some cases, reverse the conditions of soil salinization.